REAL TIME CLOCK SEBAGAI TRACKING SINAR MATAHARI PADA SOLAR CELL BERBASIS MIKROKONTROLER UNTUK LAMPU TAMA - Moch Nur Qomaruddin; Matlubul Khairi; Sulistiyanto Sulistiyanto (Universitas Islam Balitar Blitar, 2019)
One of the new and renewable energy is the utilization of sunlight into electricity. which can be used to be converted into electrical energy using solar panels. The installation of solar panels installed for garden lights so far is often still placed in a static (silent) position at an angle of 90⁰, while the sun moves from sunrise to sunset. Because it will cause maximum energy absorption in solar panels which are placed in a static position only at 12:00. To overcome this problem a system is needed to track the position of the sun so that it is always perpendicular to the surface of the solar panel. Design and build garden lights with a solar light tracking system on a microcontroller-based solar panel will later be made to move because it follows the direction of the sun's movement every hour, from rising to setting. This tool will detect the time setting inputted by Real Time Clock (RTC) which is then processed by a microcontroller to drive a servo motor that functions as a solar panel drive machine so that the position of the solar panel will always be perpendicular to the sun. throughout the day and the absorption of energy in solar panels will be more leverage. From the results of tests that have been done, the increase in the voltage of solar panels using a tracking system compared to solar panels without using a tracking system is 7.85%.